2002
DOI: 10.1016/s0014-5793(02)02255-x
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐evoked phospholipase C stimulation and adenylyl cyclase inhibition in glioma C6 cells occur through two distinct nucleotide receptors, P2Y1 and P2Y12

Abstract: In this study we characterized the subtypes of nucleotide P2Y receptors that respond to ADP in glioma C6 cells. Direct visualization of phosphatidylinositol 4,5-bisphosphate at the cell surface revealed that extracellular ADP activates phospholipase C (PLC). Knock-down of P2Y 1 receptor with antisense oligonucleotide, as well as treatment with MRS2179 and pyridoxal-phosphate-6-azophenyl-2P P,4P P-disulfonic acid (P2Y 1 antagonists), attenuates receptor-mediated PLC activity. Adenylyl cyclase inhibition by ADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…2MeSADP is a specific agonist of ADP-sensitive receptors: P2Y 1 (coupled to G q ), P2Y 12 (coupled to G i ) and P2Y 13 (coupled to G i ) [15,22,23]. As it is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2MeSADP is a specific agonist of ADP-sensitive receptors: P2Y 1 (coupled to G q ), P2Y 12 (coupled to G i ) and P2Y 13 (coupled to G i ) [15,22,23]. As it is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that both the ADP-or 2MeSADP-induced stimulation of P2Y 1 , and the ATP-or UTP-induced stimulation of P2Y 2 , initiate typical biphasic Ca 2+ responses [8,10,[13][14][15]. In contrast, the presence and activity of P2X receptors in glioma C6 cells is weakly documented [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most P2YRs are coupled to G␣ q proteins and thus to the activation of phospholipase C␤ (PLC␤) and generation of diacylglycerol and inositol-3,4,5-trisphosphate, ultimately leading to the activation of PKC and release of Ca 2ϩ from internal stores (1). Some P2YRs, including P2Y 1 , P2Y 2 , P2Y 12 , and P2Y 13 , are also known to couple to G␣ i and the inhibition of adenylyl cyclase (2)(3)(4)(5). The purinergic P2YR type 1 (P2Y 1 R) subtype is abundantly expressed in a number of tissues, including the CNS (6,7), where it plays a key role in the transmission of astrocytic Ca 2ϩ waves (8), activation of mitogenic responses in astrocytes to brain trauma (9), inhibition of neuronal N-type voltage-activated Ca 2ϩ channels (10), and embryonic brain development (11).…”
mentioning
confidence: 99%
“…Our studies using in situ hybridization and reverse transcriptase polymerase chain reaction with rodent brain slices have shown high levels of P2Y 2 R expression in the hippocampus and cerebellum [20], and P2Y 2 R expression can be significantly upregulated in mouse cortical neurons by the proinflammatory cytokine interleukin-1β (IL-1β) [48]. P2YRs have been shown to be coupled either directly or indirectly to G q , G i , G o , and G 12 protein activation and downstream signaling pathways associated with alterations in PLC or adenylyl cyclase activities [1,20,[69][70][71]. The agonist selectivity of P2YR subtypes varies widely, in contrast to P2X receptors [1]; for example, the P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 14 receptor subtypes can be activated by uridine nucleotides or UDP-glucose that are ineffective agonists of all P2X and four P2Y receptor subtypes [1,4,19,20,56,70,[72][73][74].…”
Section: P2 Receptors In the Cnsmentioning
confidence: 99%